Kajian Komoditas Unggulan Kehutanan dalam Mendukung Industri Kreatif Batik Kayu Kabupaten Gunungkidul: Identification of Leading Forest Commodities in Supporting ‘Batik’ Wood Creative Industry in Gunungkidul Regency - Mohammad Reza; Fardiah Qonita Ummi Naila (P4W LPPM IPB, 2020)
Identification of Leading Forest Commodities in Supporting ‘Batik’ Wood Creative Industry in Gunungkidul Regency The forestry sector is one of the sectors that has a role in increasing revenue in Gunungkidul Regency, contributing more than a quarter of the regency’s GRDP with main commodities of mahogany, acacia, and sengon. With a forest area of ​​56,592 Ha, it is possible for Gunungkidul Regency to produce large amounts of wood. Wood produced in Gunungkidul Regency are processed into wood-derived products in the form of wooden batik handicrafts, with an average annual turnover of Rp 4,134,801,000.00. This study aims to identify leading commodities using Location Quotient method and to provide land suitability factor for forestry commodities as batik wood industry raw material. Secondary data and primary data are used in this study. Secondary data were obtained through data collection from related institutions, such as the Office of Cooperatives and SMEs of Gunungkidul Regency and Gunungkidul Regency in Figures, Meanwhile, primary data were sourced from interviews. From the results of the study, it was concluded that mahogany and acacia are leading commodities compared to sengon. The implications of this research are expected to be input for the formulation of local government strategies, as well as for batik wood craft producers concentrated at Patuk District in developing the creative economy sector using raw material from Gunungkidul Regency.